MOF-derived carbon membranes for catalytic ozonation: Site-dependent evolution of surface atomic oxygen enables efficient water purification - Guanjin Liu; Linlin Zang; Dongwei Lu; Yinkun Sun; Hui Zhang; Yichao Hu; Zhiyu Sun; Wei Wang; Zhiqiang Sun; Jun Ma (Water Research, 2026)

Effects of evidence-based perineal massage on maternal and neonatal physiological outcomes and childbirth experience in primiparous women: A quasi-experimental study - Yuxuan Li; Linlin Cao; Hongxiao He; Haishan Wei; Hong Lu; Shenglian Ni; Jie Lu; Ruiqing Dong; Mengting Wang; Xiaoding Zhou (Next Research, 2026)

A dual-modified NASICON cathode achieving 15,000 cycles and wide-temperature operation (−20 to 55 °C) for practical sodium-ion batteries - Linying Yuan; Yuping Liao; Bing Han; Tianchen Shen; Kai Wang; Luyang Chen; Shigang Lu; Linlin Wang (Chemical Engineering Journal, 2026)

5-FU chemotherapy induces functional CD7+ and IL7R+ CTLs infiltration to suppress colorectal tumor progression - Yanmin Wu; Yan Li; Xufeng Yao; Yiyang Pan; Linlin Chen; Jian Zhang; Boyu Luo; Yue Teng; Mingqing Zhang; Chunwan Lu (Science China Life Sciences, 2026)

Prescription principle, phytochemistry, pharmacological activities and clinical applications of Huangqin decoction: a comprehensive review - Yan Fang; Haizhen Liang; Linlin Lu; Xijie Tian; Yuting Zhang; Junyu Zhang; Zhifeng Dai; Xiaojuan Chen; Juan Song; Tao Su; Zhongqiu Liu; Baiping Ma (Phytochemistry Reviews, 2026)

Spatial heterogeneity of wildfires in Southern China during the Last Glacial Maximum - Binxu Liu; Jia Liu; Xingyuan Qin; Linlin Chen; Jiaxi Zhou; Zhiyun Lu; Robert A. Spicer; Shufeng Li; Tao Su (Global and Planetary Change, 2026)

Antibacterial and antioxidant activity of ginsenosides from ginseng rootlets and their application in beef preservation - Junshun Zhang; Maoyu Wang; Suwan Lu; Yuhui Zhi; Luchen Bi; Yuxian Wang; Linlin Yin; Yi Wang; Zhina Chen (World Journal of Microbiology and Biotechnology, 2026)

Fouling and retention behavior of micro- and nano-plastics in gravity-driven membrane filtration - Xueying Chen; Dongwei Lu; Tongyu Li; Qingcan Zhou; Yinkun Sun; Linlin Zang; Jun Ma (Journal of Water Process Engineering, 2026)

Breaking the trade-off: A phosphorylated interpenetrating network bridging ion-conduction pathways for safe and high-performance solid-state batteries - Yuyang Wang; Linlin Wang; Jie Yang; Qiuya Wang; Junye Zhang; Cheng Liu; Zaichao Zhang; Le Xu; Rundong Chen; Tianchen Shen; Shigang Lu; Luyang Chen (Chemical Engineering Journal, 2026)

ABEEM/MM Magnesium Force Field for Proteins and Aqueous Solutions - Jing Zhang; Linan Lu; Runqiang Yu; Linlin Liu; Lei Wang; Cui Liu; Lidong Gong; Zhongzhi Yang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Comparison of Turbulent Transport Dissimilarity and the Role of Coherent Structures in the Unstable Surface Layer Between Urban and Rural Areas - Qiyue Sun; Lu Zhang; Jiesheng Xue; Linlin Wang; Yubin Li; Yuanjian Yang (Boundary-Layer Meteorology, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Compositing high-resolution SDGSAT-1 nighttime light data by ranking of structural image features - Martino Pesaresi; Johannes H. Uhl; Linlin Lu; Panagiotis Politis; Dong Liang; Michele Melchiorri; Inés Marí Rivero; Katarzyna Krasnodębska; Huadong Guo (Remote Sensing of Environment, 2026)

Polyphenol oxidase-mediated browning during storage of Pinus elliottii oleoresin: characterization of pine-needle PPO and antibrowning action of L-cysteine - Siheng Zhang; Hanxiao Liu; Jingcong Liu; Lu Qin; Xin Li; Xuanrou Wei; Xiaopeng Chen; Linlin Wang (Food Bioscience, 2026)

Similarity-based classification of groundwater hydrographs to reveal regional groundwater dynamics patterns in a semi-arid agricultural area - Xiangbo Meng; Xi Chen; Yonggen Zhang; Man Gao; Linlin Lu (Hydrogeology Journal, 2026)

Seven neonicotinoids and twenty-two metabolites in seven food matrices by optimized QuEChERS-HPLC-MS/MS and dietary risk assessment - Zhenzhen Zhou; Xueyan Zhao; Junfeng Lu; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie; Fajun Tian (Food Chemistry, 2026)

DKK1 expression associates with tertiary lymphoid structure maturity in non-small cell lung cancer - Lin Ma; Linlin Yang; Junxu Wen; Fei Lu; Jinming Yu; Xiangjiao Meng (Apoptosis, 2026)

Integrating SDGSAT-1 glimmer imagery with Sentinel-1/2 data for high-resolution building height estimation - Zilu Li; Huadong Guo; Linlin Lu; Yifang Ban; Qi Zhu; Dong Liang (Remote Sensing of Environment, 2026)

Chemical and sensory characteristics of Baiye No.1 (BY1H) yellow tea: Insights into flavoring mechanism and quality valuation - Shiyu Zhang; Xinzhuan Yao; Yanxia Wang; Muhammad Safiullah Virk; Shiyu Tian; Zhenkedai Yuan; Qihong Zou; Linlin Li; Shenyuan Ye; Hu Tang; Litang Lu (Food Bioscience, 2026)

Synergistic effects of crystal-facet on dehalogenation kinetics and poison tolerance of Pd-based electrocatalytic membranes for efficient removal of halogenated pollutants - Yinkun Sun; Dongwei Lu; Xianci Pan; Rongxin Zeng; Zhiyu Sun; Xueying Chen; Yumei Wang; Qingcan Zhou; Yichao Hu; Linlin Zang; Guanjin Liu; Jun Ma (Chemical Engineering Journal, 2026)

An overview of GNSS for tsunami early warning: From lithosphere to ionosphere - Kejie Chen; Haishan Chai; Jiafeng Li; Guoguang Wei; Mingzhe Lyu; Wenfeng Cui; Chuang Shi; Linlin Li; Peitao Wang; Wei Lu; Jian Lin (Science China Earth Sciences, 2026)

Integrated multi-energy hybrid systems for net-zero buildings: Dynamic simulation, lifecycle 4E assessment, and multi-objective optimization - Manfeng Li; Mengke Liu; Guofeng Zhou; Linlin Zhang; Panpan Li; Yiji Lu (Energy and Buildings, 2026)

Black phosphorus quantum dots regulate inflammation and neural stem cells differentiation via Notch1 signaling through cell adhesion - Lu Chen; Yongyuan Guo; Lusen Shi; Shiji Zhang; Linlin Jiang; Yong Chang; Haoran Liu; Zihang Wang; Na Li; Shiqing Feng (Chemical Engineering Journal, 2026)

Drug screening reveals the mechanism of toyocamycin-induced apoptosis in triple-negative breast cancer organoids - Houshi Ma; Linlin Lu; Yuqing Tu; Xiaoran Chang; Huabin Jiang; Tianhang Yang; Shun Wang; Jinxian Wang; Jinbing Xue; Yan Chen; Gangyin Luo (Toxicology and Applied Pharmacology, 2026)

Carbonized polymer dots as drivers of modernization in Chinese Herbal Medicine - Linlin Zhang; Ying Cheng; Xin Yang; Xiaoyu Chang; Siyu Lu; Bai Yang; Xiaoli Qu (Science Bulletin, 2026)

Interactive effect of children’s copper exposure and socioeconomic status on preschoolers’ cognitive development - Hualong Zhen; Linlin Zhu; Xuemei Hao; Jingru Lu; Yufan Guo; Chunmei Liang; Juan Tong; Fangbiao Tao; Jiong Li; Kun Huang (NeuroToxicology, 2026)

Tracing nitrate sources and transformations using nitrogen and oxygen isotopes in the second largest freshwater lake of China - Zhengjie Li; Guitao Shi; Yilan Li; Linlin Song; Yanhua Zhang; Yi Shi; Wei Zhang; Shuguang Liu; Weizhi Lu (Journal of Hydrology, 2026)

A machine learning-based model for aerosol scattering hygroscopic growth factor (f(RH)) prediction in Beijing urban area - Hongfei Tong; Xinyao Hu; Can Xia; Xiaojing Shen; Yangmei Zhang; Quan Liu; Lei Liu; Linlin Liang; Jiayuan Lu; Huizheng Che; Xiaoye Zhang; Junying Sun (Atmospheric Environment, 2026)

Preparation of a Near-infrared Probe Based on Triphenylamine Thiophene and its Use for the Fluorescence Imaging of H2S in Living Cells - Lu Yang; Huan Li; Miaomiao Li; Aoxiang Fu; Shiqiong Bai; Jing Li; Linlin Yang; Guangjie He (Journal of Fluorescence, 2025)

Apple diameter prediction during mechanical picking based on flexible force-sensing and CNN-BiLSTM-Attention method - Mingyang Lu; Linlin Sun; Haidi Chu; Mochen Liu; Jing Wang; Hongjian Zhang; Zhanhua Song; Yao Lu; Jinxing Wang; Yinfa Yan (Computers and Electronics in Agriculture, 2025)

Zein/eugenol electrospun mats on gelatin/laponite substrate for developing bilayer functional food packaging - Minmin Chen; Linlin Li; Wei Ji; Wensheng Lu; Xiaochao Tang; Suwei Jiang; Hualin Wang (Food Research International, 2025)

Tracking Browning mechanistic pathway of postharvest pine resin using comparative metabolomics - Xin Li; Junsheng Lu; Junmei Ye; Yibin Qin; Xiaopeng Chen; Jiezhen Liang; Linlin Wang (Food Chemistry, 2025)

OWTDNet: A Novel CNN-Mamba Fusion Network for Offshore Wind Turbine Detection in High-Resolution Remote Sensing Images - Pengcheng Sha; Sujie Lu; Zongjie Xu; Jianhai Yu; Lei Li; Yibo Zou; Linlin Zhao (Journal of Marine Science and Engineering, 2025)
Real-time monitoring of offshore wind turbines (OWTs) through satellite remote sensing imagery is considered an essential process for large-scale infrastructure surveillance in ocean engineering. Current detection systems, however, are constrained by persistent technical limitations, including prohibitive deployment costs, insufficient discriminative power for learned features, and susceptibility to environmental interference. To address these challenges, a dual-branch architecture named OWTDNet is proposed, which integrates global contextual modeling via State Space Models (SSMs) with CNN-based local feature extraction for high-resolution OWTs detection. The primary branch utilizes a Mamba-structured encoder with linear computational complexity to establish long-range spatial dependencies, while an auxiliary Blurring-MobileNetv3 (B-Mv3) branch is designed to compensate for the local feature extraction deficiencies inherent in SSMs. Additionally, a novel Feature Alignment Module (FAM) is introduced to systematically coordinate cross-modal feature fusion between Mamba and CNN branches through channel-wise recalibration and position-aware alignment mechanisms. This module not only enables complementary feature integration but also enhances turbine-specific responses through attention-driven feature modulation. Comprehensive experimental validation demonstrated the superiority of the proposed framework, achieving a mean average precision (AP) of 47.1% on 40,000 × 40,000-pixel satellite imagery, while maintaining practical computational efficiency (127.7 s per image processing time).

Gaussian Building Mesh (GBM): Extract a building’s 3D mesh with Google Earth and Gaussian Splatting - Kyle Gao; Dening Lu; Hongjie He; Liangzhi Li; Linlin Xu; Michael A. Chapman; Jonathan Li (Remote Sensing Applications: Society and Environment, 2025)

Investigating the aroma transition during rapid mango ripening driven by dynamic catabolism of fatty acids - Yuanping Wang; Zhenjiang Zhou; Yonghao Liu; Rongli Pang; Xi Zhao; Qi Chen; Linlin Guo; Baiyi Lu (Food Chemistry, 2025)

Hyperbaric oxygen treatment mitigates gut dysbiosis of mice with spinal cord injury - Mo Liu; Lu Yang; Ding Nan; Linlin Ma; Jing Zhang; Fang Liang; Jing Yang; Xuehua Liu (Journal of Molecular Medicine, 2025)

A Study on Energy Loss and Transient Flow Characteristics of a Large Volute Centrifugal Pump During Power-Off Process Under Cavitation Conditions - Qingzhao Pang; Desheng Zhang; Gang Yang; Xi Shen; Qiang Pan; Linlin Geng; Qinghui Lu (Journal of Marine Science and Engineering, 2025)
A novel pumped storage system using centrifugal pumps to transfer water between reservoirs in coastal hydropower plants has significantly mitigated grid instability. However, frequent start–stop operations of large vertical centrifugal pumps, which serve as the core equipment, severely affect the operational stability of these systems. In this study, the intrinsic connection between the cavitating flow field and irreversible losses during the process was analyzed using the entropy production theory. The time–frequency characteristics of pressure pulsation in pump were analyzed by using the continuous wavelet transform. The results indicate that with the reduction in the flow rate and rotational speed, the sheet cavitation at the impeller inlet rapidly weakens until it vanishes. The cavity cavitation within the draft tube commences to emerge in the turbine mode. Separation vortices are formed due to the mismatch in the flow angle at the impeller outlet. These vortices induce local cavitation, causing both a rapid energy loss increase and high-amplitude, low-frequency pressure pulsations. During transient processes, flow instabilities induce high-amplitude, low-frequency pressure pulsations within the stay vane region, with maximum amplitude attained during runaway condition. The research results provide a theoretical foundation for the stable operation of centrifugal pumps.

Enhancing the identification of malonylation sites using AlphaFold2 and ensemble learning - Linlin Xu; Yuting Qian; Jiayi Yang; Xiaowei Xu; Zhiqiang Li; Yanhan Wang; Enhui Lv; Xingxing Kang; Hongwei Zhang; Yaping Lu; Fei Wang; Xin Liu (Molecular Diversity, 2025)

Land use carbon emission projections in shared socioeconomic and representative concentration pathways: Relationship with urbanization in Chinese megacities - Yu Yao; Linlin Lu; Zongtang Fu; Fang Chen; Ran Wang; Qingting Li (Land Use Policy, 2025)

Efficient degradation of tetracycline using boron assistant Co3O4 activated PAA: Formation of B-O-Co and accelerated electron transfer - Peng Lu; Jialin Jiang; Linlin Miao; Yun Guo; Haizhu Chen; Shuai Zhou; Jiutao An (Journal of Environmental Chemical Engineering, 2025)

Novel thin film nanocomposite membranes developed via polydopamine nanoparticles, Halloysite nanotubes and Cu-MOF nanosheets for dye removal - Junfeng Zheng; Jinyu Liu; Zikang Qin; Yulei Ma; Yahui Yang; Linlin Yang; Hang He; Zhongde Dai; Wenju Jiang; Lin Yang; Lu Yao; Bo Tang (Journal of Environmental Chemical Engineering, 2025)

Characterization of TGFβ Signaling Components in Large Yellow Croaker (Larimichthys crocea) and Their Role in Growth and Body Shape Regulation - Xuyang Jiang; Lu Zhang; Xin Hu; Mingchao Cui; Jie Li; Huang Liu; Linlin Yao (Journal of Marine Science and Engineering, 2025)
The transforming growth factor β (TGFβ) signaling axis plays a pivotal role in orchestrating a wide array of biological functions, encompassing cellular growth, proliferation, and differentiation. The aim of the present study was to identify the members of TGFβ signaling pathway and their expression patterns in large yellow croaker (Larimichthys crocea) under different culture modes. TGFβ signaling pathway and their expression patterns in fish reared under two different culture modes: Group N (2400 fish in a 120 m3 cage) and Group V (168,000 fish in a 5600 m3 aquaculture vessel). After 120 days, we analyzed 15 fish from each group and found that Group V exhibited faster growth and a slender body shape compared to Group N. Bioinformatics analysis identified 48 TGFβ superfamily members in L. crocea, including 21 ligands, 10 receptors, and 3 Smads. mRNA expression levels indicated that these signaling molecules influence growth rate and body shape through five distinct ligand–receptor–R-Smad pathways, with the INHBB-, Nodal-, and GDF3-ACVR2A-ALK4-Smad2 axis playing a predominant role in regulating these traits.

In-situ phenolics enrichment of Camellia oleifera Abel oil via novel aqueous enzymatic extractions and its potential mechanism - Linlin Liu; Chengyu Jin; Yuanchao Lu; Ningxiang Yu; Xiaohua Nie; Qin Ye; Yuanxiang Jin; Xianghe Meng (Food Chemistry, 2025)

Trophic niche variation in springtails across soil depth - Jing-Zhong Lu; Melissa Jüds; Linlin Zhong; Johannes Lux; Stefan Scheu; Amandine Erktan (European Journal of Soil Biology, 2025)

Melanoidins induced transformation of protein and polysaccharide during thermal hydrolysis-pyrolysis of sludge via non-covalent forces - Yimeng Jiao; Yifei Wu; Ziyang Dong; Jinxuan Ning; Jialin Wang; Lu Liu; Zhengda Lin; Yu Tian; Linlin Yin; Jun Zhang (Chemical Engineering Journal, 2025)

Determination of the deposition of urban submicron aerosols in the human respiratory tract considering hygroscopic growth - Aoyuan Yu; Jiayuan Lu; Xiaojing Shen; Xinyao Hu; Yangmei Zhang; Quan Liu; Hongfei Tong; Linlin Liang; Lei Liu; Qianli Ma; Lujie Han; Huizheng Che; et al. (Atmospheric Environment, 2025)

Interpretability and identification of dimorphism in morphological indexes of Larimichthys crocea based on machine learning models - Liguo Ou; Linlin Lu; Weiguo Qian; Bilin Liu (Fisheries Research, 2025)

Norgestrel shows androgenic properties and triggers reproductive neuroendocrine toxicity in the testes of Pacific oysters (Crassostrea gigas) - Yan Fang; Baojun Liu; Juan Wang; Haoyang Zhong; Linlin Fan; Yuchao Huang; Changkun Chen; Songtao Lu; Tao Zheng (Journal of Hazardous Materials, 2025)

A preliminary study on the community structure of culturable planktonic and attached bacteria in the harbor of Qingdao, China - Shide Ma; Linlin Zhang; Yimeng Zhang; Yu Tai; Wen Han; Jinfeng Yang; Xin Shi; Bochao Lu; Jizhou Duan (Acta Oceanologica Sinica, 2025)

Impacts of spatial resolutions of UAV-LiDAR-derived DEMs on erosion modelling in the hilly and gully Loess Plateau - Wenli Li; Pengfei Li; Lu Yan; Jinfei Hu; Leiqin Wang; Dou Li; Yang Dan; Linlin Huang; Guangju Zhao (CATENA, 2025)

Global variations of urban form: Characterization and quantification through intelligent remote sensing image analysis - Jie Chen; Geng Sun; Yongze Song; Yinxia Cao; Cheolhee Yoo; Ya Guo; Chunhong Zhao; Linlin Lu; Qihao Weng (Sustainable Cities and Society, 2025)

Lacticaseibacillus paracasei SB27 enhances its gastrointestinal tolerance, adhesion and colonization by producing biofilm - Yinxue Liu; Linlin Hao; Yisuo Liu; Lu Jiang; Huaxi Yi (Food Bioscience, 2025)

Performance and mechanism of tris(2-chloropropyl) phosphate (TCPP) removal in an iron-carbon microelectrolysis constructed wetland system - Yongqiang Wang; Linlin Li; Xiaochun Guo; Aiwen Wang; Yunhao Pan; Jun Ma; Shaoyong Lu; Dongmei Liu (Chemical Engineering Journal, 2025)

Inactivation activity and mechanism of natural antimicrobial agents against Alicyclobacillus spp. in apple juice - Rui Cai; Linlin Gao; Yuxiang Zhang; Lu Cui; Yahong Yuan; Zhouli Wang; Tianli Yue (Food Control, 2025)

The influence of 2,6-Di-tert-butyl-p-cresol stress on the microalga Phaeodactylum tricornutum and phycosphere bacteria community - Xiao Lu; Jie Liu; Xinfeng Xiao; Jianliang Xue; Dongle Cheng; Linlin Zhang (World Journal of Microbiology and Biotechnology, 2025)

Application of artificial intelligence in fish information identification: a scientometric perspective - Liguo Ou; Linlin Lu; Weiguo Qian; Bilin Liu (Frontiers in Marine Science, 2025)
In the context of the growing demand for the sustainable development and conservation of fish stocks, artificial intelligence (AI) technologies are essential for supporting scientific fish stock management. Artificial intelligence technology provides an effective solution for the intelligent recognition of fish information. This study used bibliometric analysis to review a sample of 719 scientific articles from the WoSCC (Web of Science Core Collection) database from 2014-2024. The results revealed a significant increase in the number of publications from 2014-2024, with publications mainly from China, the USA (the United States) and other developed countries. The top three impactful journals are Ecological Informatics, Computers and Electronics in Agriculture and the ICES Journal of Marine Science. The most frequent keyword co-occurrence analysis was deep learning, and the best keyword clustering effect was computer vision. The findings indicate that this bibliometric evaluation provides a holistic visualization of the research frontier of AI in fish information identification, and our findings underscore the growing global importance of AI in fish information identification research and highlight publication trends, hotspots, and future research directions in this area. In conclusion, our findings provide valuable insights into the emerging frontiers of AI-based fish information identification.

Development and validation of a prediction model for the depressive symptom risk in commercial airline pilots - Jie Zhang; Xuhua Chen; Lin Zhang; Haodong Qi; Erliang Zhang; Minzhi Chen; Yiran Wang; Yunfei Li; Yan Chen; Qingqing Duan; Feng Shi; Linlin Wang; et al. (EPMA Journal, 2025)

Diffusion coefficients of water in CO2 under the condition of CO2 sequestration in saline aquifers - Zhe Wang; Linlin Lin; Huirong Guo; Wanjun Lu (Journal of Hydrology, 2025)

Magnetic resonance spectroscopy for discriminating primary angiitis of the central nervous system from gliomas and lymphomas - Ping Lu; Lingyun Cui; Lulin Zhang; Huabing wang; Linlin yin; Decai Tian; Xinghu Zhang (Acta Neurologica Belgica, 2025)

Residual behaviors and health risk assessment of dinotefuran, flonicamid, and their metabolites during apple growth, storage, and processing - Fajun Tian; Zhenzhen Zhou; Junfeng Lu; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie (Food Research International, 2025)

Butyrylated modification of corn starch alleviates autism-like behaviors by modulating 5-hydroxytryptamine metabolism and gut-brain neural activity - Wentian Li; Qingmin Kong; Min Guo; Linlin Wang; Peijun Tian; Jingyu Lu; Jianxin Zhao; Wei Chen; Gang Wang (Carbohydrate Polymers, 2025)

Ecological restoration orientated application and modification of constructed wetland substrates - Jiapeng Yang; Shuiping Cheng; Yongqiang Wang; LinLin Li; Shaoyong Lu (Environmental Research, 2025)

Complementary nitrogen use by legume and grass enhances plant productivity irrespective of earthworm species - Linlin Zhong; Jing-Zhong Lu; Stefan Scheu; Melanie M. Pollierer (Applied Soil Ecology, 2025)

Provincial localization framework for SDGs in China: Enhancing support for sustainable governance - Wen Song; Shisong Cao; Mingyi Du; Linlin Lu; Huadong Guo; Sirui Wang; Yue Liu; Xiaoxuan Li (Applied Geography, 2025)

High litter quality enhances plant energy channeling by soil macro‐detritivores and lowers their trophic position - Linlin Zhong; Thomas Larsen; Jing‐Zhong Lu; Stefan Scheu; Melanie M. Pollierer (Ecology, 2025)
Detritus‐based resources, that is, plant litter, are a major energy source for many living organisms and are considered to be a key determinant of primary production and nutrient cycling. Earthworms are among the most important macro‐detritivores in terrestrial food webs and play a crucial role in facilitating these processes in terrestrial ecosystems. Yet, the influence of litter quality on earthworm nutrition, and consequently on soil food web dynamics, has remained largely underexplored, mainly for methodological reasons. Here, we combined bulk and compound‐specific stable isotope analysis of amino acids to investigate the dietary contribution of different quality litter resources to earthworm species of different ecological groups. Our findings show that earthworms acquired most essential amino acids from bacterial (~60%) and plant (~30%) resources, with the latter increasing in importance with higher litter quality, resulting in lower trophic positions across earthworm species. The high bacterial contribution to earthworms corresponds to the dominance of bacteria in the experimental soil, suggesting that bacteria served as an important intermediate link in transferring detritus‐based resources to earthworms. Bacterial contributions were notably higher in the soil‐feeding earthworm species than in the litter‐feeding earthworm species, likely due to more pronounced ingestion of soil by soil‐feeding earthworms. Overall, our study indicates that a major group of soil macro‐detritivores, earthworms, receive detrital resources via the bacterial energy channel. Further, it underscores the important role of litter quality in shaping the trophic niches of detritivores, thereby influencing the overall structure of soil food webs.

Lactic acid bacteria in relieving constipation: mechanism, clinical application, challenge, and opportunity - Tong Zhang; Wenxu Liu; Huimin Lu; Ting Cheng; Linlin Wang; Gang Wang; Hao Zhang; Wei Chen (Critical Reviews in Food Science and Nutrition, 2025)

A comprehensive review on iron‒carbon microelectrolysis constructed wetlands: Efficiency, mechanism and prospects - Yongqiang Wang; Linlin Li; Xiaochun Guo; Aiwen Wang; Yunhao Pan; Jun Ma; Shaoyong Lu; Dongmei Liu (Water Research, 2025)

Metagenomics and metaproteomics reveal the effects of sludge types and inoculation modes on N,N-dimethylformamide degradation pathways and the microbial community involved - Yunchuan Xian; Linlin Cao; Yuxiang Lu; Qiuhong Li; Chengyuan Su; Yuan He; Guangrong Zhou; Shenglong Chen; Shu Gao (Journal of Hazardous Materials, 2025)

Individual tree species classification using low-density airborne multispectral LiDAR data via attribute-aware cross-branch transformer - Lanying Wang; Dening Lu; Linlin Xu; Derek T. Robinson; Weikai Tan; Qian Xie; Haiyan Guan; Michael A. Chapman; Jonathan Li (Remote Sensing of Environment, 2024)

High mechanical property, hydrophobic and fire-retardant cellulose film derived from kenaf degumming wastewater - Shixing Wang; Xiaolong Qiao; Linlin Li; Hailong Lu; Yuanming Zhang; Guangting Han; Haoxi Ben; Wei Jiang (Journal of Environmental Chemical Engineering, 2024)

Umbrella effect of spotted seal conservation and achieving 30 × 30 targets in the Yellow Sea ecoregion - Hongfei Zhuang; Fangyuan Qu; Zhichuang Lu; Linlin Zhao; Zhaohui Zhang (Reviews in Fish Biology and Fisheries, 2024)

Biocontrol potential of plant growth-promoting rhizobacteria against plant disease and insect pest - Qinhao Jian; Tongrui Zhang; Yingying Wang; Li Guan; Linlin Li; Longna Wu; Shiyan Chen; Yumei He; Hong Huang; Shugang Tian; Hu Tang; Litang Lu (Antonie van Leeuwenhoek, 2024)

Characteristics of iron-sulfur metabolism and acid-producing microorganisms in groundwater contaminated by acid mine drainage in closed coal mines - Yanchang Huang; Ping Lu; Feng Zhang; Hao Chen; Wenliang Zhang; Linlin Lin; Hepeng Xu; Haoran Ding; Tianhang Cheng (Groundwater for Sustainable Development, 2024)

High-value multilayer graphene oxide prepared by catalytic pyrolysis of petroleum tar and applications: Trash to treasure - Lu Liu; Jialin Wang; Yifei Wu; Linlin Yin; Wei Zuo; Yu Tian; Jun Zhang (Chemical Engineering Journal, 2024)

Quantifying the changes in solute transport caused by human influence on river connectivity in inland river basins - Wenhao Zhang; Guofeng Zhu; Ling Zhao; Lei Wang; Dongdong Qiu; Linlin Ye; Siyu Lu; Xinrui Lin (CATENA, 2024)

Integrated proteome and pangenome analysis revealed the variation of microalga Isochrysis galbana and associated bacterial community to 2,6-Di-tert-butyl-p-cresol (BHT) stress - Linke Guo; Shuangwei Li; Dongle Cheng; Xiao Lu; Xinying Gao; Linlin Zhang; Jianjiang Lu (World Journal of Microbiology and Biotechnology, 2024)

Biomass-derived carbon dots with pharmacological activity for biomedicine: Recent advances and future perspectives - Yue Liu; Linlin Zhang; Huijuan Cai; Xiaoli Qu; Junbiao Chang; Geoffrey I.N. Waterhouse; Siyu Lu (Science Bulletin, 2024)

Effects of storage and processing on the residual distribution and behavior of five preservatives and their metabolites in pomegranate - Fajun Tian; Junfeng Lu; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie (Food Chemistry, 2024)

Influence of mountain orientation on precipitation isotopes in the westerly belt of Eurasia - Longhu Chen; Guofeng Zhu; Qin Qin Wang; Linlin Ye; Xinrui Lin; Siyu Lu; Yinying Jiao; Rui Li; Gaojia Meng; Yuhao Wang; Jiangwei Yang; Chen Jia (Global and Planetary Change, 2024)

Experimental study and design methodology of sacrificial-energy dissipation beam-column joint - Xinzheng Lu; Xinlei Jin; Yuan Tian; Linlin Xie; Yixing Wang (Engineering Structures, 2024)

Promoting the systematic utilization of reclaimed asphalt pavement (RAP) through waste asphalt-derived carbon in batteries applications - Danqing Li; Xin He; Hu Fu; Wenqi Tan; Shigang Lu; Linlin Wang; Mei Ding; Chunhui Gao; Chuankun Jia (Chemical Engineering Journal, 2024)

Myosin Va-dependent Transport of NMDA Receptors in Hippocampal Neurons - Ru Gong; Linwei Qin; Linlin Chen; Ning Wang; Yifei Bao; Wei Lu (Neuroscience Bulletin, 2024)
N-methyl-D-aspartate receptor (NMDAR) trafficking is a key process in the regulation of synaptic efficacy and brain function. However, the molecular mechanism underlying the surface transport of NMDARs is largely unknown. Here we identified myosin Va (MyoVa) as the specific motor protein that traffics NMDARs in hippocampal neurons. We found that MyoVa associates with NMDARs through its cargo binding domain. This association was increased during NMDAR surface transport. Knockdown of MyoVa suppressed NMDAR transport. We further demonstrated that Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) regulates NMDAR transport through its direct interaction with MyoVa. Furthermore, MyoVa employed Rab11 family-interacting protein 3 (Rab11/FIP3) as the adaptor proteins to couple themselves with NMDARs during their transport. Accordingly, the knockdown of FIP3 impairs hippocampal memory. Together, we conclude that in hippocampal neurons, MyoVa conducts active transport of NMDARs in a CaMKII-dependent manner.

Differences and implications of strontium distribution coefficient on various granite compositional materials - Fangfei Cai; Xiaoying Zhang; Funing Ma; Linlin Qi; Di Lu; Zhenxue Dai (Environmental Science and Pollution Research, 2024)

Dissipation behavior and risk assessment of imidacloprid and its metabolites in apple from field to products - Fajun Tian; Junfeng Lu; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie (Chemosphere, 2024)

Low energy-consumption oriented membrane fouling control strategy in anaerobic fluidized membrane bioreactor - Lu Liu; Ze Guo; Yihe Wang; Linlin Yin; Wei Zuo; Yu Tian; Jun Zhang (Chemosphere, 2024)

Fabrication of stable spherical soybean lipophilic protein nanogel for curcumin delivery: Carbony oxygen and aromatic ring flexibility binding to the beta−barrel - Jianhua Zeng; Junzhe Zou; Lanwei Zhang; Jinlong Zhao; Linlin Liu; Gen Lu; Bingyu Sun; Yanguo Shi; Xiuqing Zhu; Pimin Gong (Food Structure, 2024)

A critical review of characteristics of domestic wastewater and key treatment techniques in Chinese villages - Jing Zhang; Yungeng Jiang; Heyu Zhang; Dan Feng; Hongling Bu; Linlin Li; Shaoyong Lu (Science of The Total Environment, 2024)

Photosynthetic microalgae microbial fuel cells for bioelectricity generation and microalgae lipid recovery using Gd-Co@N-CSs/NF as cathode - Linlin Qin; Yiming Qin; Na Cui; Xu Han; Haoran Lu; Tong Yang; Wenyan Liang (Chemical Engineering Journal, 2024)

Activatable theranostic nanoprobes for Fluorescence/MR imaging and microenvironment remodeling of early cartilage degeneration - Xiuli Zhang; Manman Xie; Linlin Li; Wenlou Liu; Peng Xu; Zuohui Zhang; Yue Dai; Dongxu Wang; Li Lu; Kai Xu; Jingjing Li (Chemical Engineering Journal, 2024)

A transferable approach to assessing green infrastructure types (GITs) and their effects on surface urban heat islands with multi-source geospatial data - Linlin Lu; Huadong Guo; Qihao Weng; Carlos Bartesaghi-Koc; Paul Osmond; Qingting Li (Remote Sensing of Environment, 2024)

Nitrogen isotopic characteristics of aerosol ammonium in a Chinese megacity indicate the reduction from vehicle emissions during the lockdown period - Zhengjie Li; Hongwei Xiao; Wendell W. Walters; Meredith G. Hastings; Juan Min; Linlin Song; Weizhi Lu; Libin Wu; Wende Yan; Shuguang Liu; Yunting Fang (Science of The Total Environment, 2024)

Mild low-temperature photothermal therapy demonstrated a distinctive 'hot spring' effect in the multichannel regulation of atherosclerosis instead of inducing foam cell apoptosis - Jie Sheng; Ziyue Zu; Jianchen Qi; Yugang Zhang; Haoguang Wu; Zhicheng Wang; Yu Miao; Tao Zheng; Sheng Wang; Linlin Zhang; Guangming Lu; Longjiang Zhang (Chemical Engineering Journal, 2024)

Impact analysis of hydraulic residence time and dissolved oxygen on performance efficiency and microbial community in N, N-dimethylformamide wastewater treated by an AnSBR-ASBR - Yuchen Wang; Linlin Cao; Yiying Lu; Junjie Liao; Yuxiang Lu; Chengyuan Su; Shu Gao (Environmental Pollution, 2024)

Piezoelectric effect-assisted Z-scheme heterojunction ZnIn2S4/BaTiO3 for improved photocatalytic reduction of CO2 to CO - Shanyue Lu; Shengwei Zhang; Linlin Li; Cong Liu; Zhou Li; Dan Luo (Chemical Engineering Journal, 2024)

Electrocatalytic degradation of nitrogenous heterocycles on confined particle electrodes derived from ZIF-67 - Yu Liu; Linlin Qin; Yiming Qin; Tong Yang; Haoran Lu; Yulong Liu; Qiqi Zhang; Wenyan Liang (Journal of Hazardous Materials, 2024)

Investigating the role of Na-bentonite colloids in facilitating Sr transport in granite minerals through column experiments and modeling - Xiaoying Zhang; Fangfei Cai; Funing Ma; Paul Reimus; Linlin Qi; Di Lu; Mohamad Reza Soltanian; Zhenxue Dai (Journal of Hazardous Materials, 2024)

Alisol A Exerts Neuroprotective Effects Against HFD-Induced Pathological Brain Aging via the SIRT3-NF-κB/MAPK Pathway - Taotao Lu; Linlin Ding; Xiaoqing Zheng; Yongxu Li; Wei Wei; Weilin Liu; Jing Tao; Xiehua Xue (Molecular Neurobiology, 2024)
Chronic consumption of a high-fat diet (HFD) has profound effects on brain aging, which is mainly characterized by cognitive decline, inflammatory responses, and neurovascular damage. Alisol A (AA) is a triterpenoid with therapeutic potential for metabolic diseases, but whether it has a neuroprotective effect against brain aging caused by a HFD has not been investigated. Six-month-old male C57BL6/J mice were exposed to a HFD with or without AA treatment for 12 weeks. Behavioral tasks were used to assess the cognitive abilities of the mice. Neuroinflammation and changes in neurovascular structure in the brains were examined. We further assessed the mechanism by which AA exerts neuroprotective effects against HFD-induced pathological brain aging in vitro and in vivo. Behavioral tests showed that cognitive function was improved in AA-treated animals. AA treatment reduced microglia activation and inflammatory cytokine release induced by a HFD. Furthermore, AA treatment increased the number of hippocampal neurons, the density of dendritic spines, and the expression of tight junction proteins. We also demonstrated that AA attenuated microglial activation by targeting the SIRT3-NF-κB/MAPK pathway and ameliorated microglial activation-induced tight junction degeneration in endothelial cells and apoptosis in hippocampal neurons. The results of this study show that AA may be a promising agent for the treatment of HFD-induced brain aging.

Duck Tembusu virus infection activates the MKK3/6-p38 MAPK signaling pathway to promote virus replication - Yuting Cheng; Linlin Jiao; Jinying Chen; Peiyao Chen; Fang Zhou; Jilin Zhang; Mixue Wang; Qingguo Wu; Shinuo Cao; Huipeng Lu; Zhi Wu; Anping Wang; et al. (Veterinary Microbiology, 2024)

Heat stress reduces brown adipose tissue activity by exacerbating mitochondrial damage in type 2 diabetic mice - Penghua Lai; Linlin Zhang; Yan Qiu; Jie Ren; Xue Sun; Ting Zhang; Liuyi Wang; Sijie Cheng; Sijia Liu; Hongli Zhuang; Daiwei Lu; Shaoliang Zhang; et al. (Journal of Thermal Biology, 2024)

Numerical simulation and seismic performance analysis of sacrificial-energy dissipation beam-column joint - Xinlei Jin; Wenjie Liao; Yuan Tian; Linlin Xie; Xinzheng Lu (Engineering Structures, 2023)

Stable precipitation isotope records of cold wave events in Eurasia - Xinrui Lin; Guofeng Zhu; Dongdong Qiu; Linlin Ye; Yuwei Liu; Longhu Chen; Jiawei Liu; Siyu Lu; Lei Wang; Kailiang Zhao; Wenhao Zhang; Rui Li; et al. (Atmospheric Research, 2023)

Investigating the influence of bentonite colloids on strontium sorption in granite under various hydrogeochemical conditions - Fangfei Cai; Funing Ma; Xiaoying Zhang; Paul Reimus; Linlin Qi; Yu Wang; Di Lu; Hung Vo Thanh; Zhenxue Dai (Science of The Total Environment, 2023)

Dissipation and movement of soil water in artificial forest in arid oasis areas: Cognition based on stable isotopes - Dongdong Qiu; Guofeng Zhu; Xinrui Lin; Yinying Jiao; Siyu Lu; Jiatong Liu; Jiawei Liu; Wenhao Zhang; Linlin Ye; Rui Li; Qinqin Wang; Longhu Chen (CATENA, 2023)

Glyphosate induces autophagy in hepatic L8824 cell line through NO-mediated activation of RAS/RAF/MEK/ERK signaling pathway and energy metabolism disorders - Linlin Zhang; Lu Chen; Meng Qi; Fuchang Yu; Xiaotong Ni; Haozheng Hong; Haotian Xu; Shiwen Xu (Fish & Shellfish Immunology, 2023)

Experimental investigation on seismic performance of self-centering frictional cast-in-situ beam-column joints - Xiao Lu; Hang Xu; Xuemin Zhang; Linlin Xie (Engineering Structures, 2023)

Exploring the seasonality of surface urban heat islands using enhanced land surface temperature in a semi-arid city - Liying Han; Linlin Lu; Peng Fu; Chao Ren; Meng Cai; Qingting Li (Urban Climate, 2023)

Contrasting determinants of land surface temperature in three megacities: Implications to cool tropical metropolitan regions - Linlin Lu; Peng Fu; Ashraf Dewan; Qingting Li (Sustainable Cities and Society, 2023)

Citrate-enhanced leaching of arsenic from coal with simulated flue gas under UV irradiation - Shun Qiu; Zhenzhen Lu; Wenshou Sun; Linlin Tao; Jin Li; Jintong Li (Chemical Engineering Journal, 2023)

Long-term performance study applying a tandem AnSBR-ASBR to treat wastewater containing N, N-dimethylformamide: Sludge physicochemical properties, microecology, and functional genes - Linlin Cao; Chengyuan Su; Yiying Lu; Jinyan Wu; Lixin Wei; Junjie Liao; Yunchuan Xian; Shu Gao (Journal of Environmental Chemical Engineering, 2023)

Tannin alleviates glyphosate exposure-induced apoptosis, necrosis and immune dysfunction in hepatic L8824 cell line by inhibiting ROS/PTEN/PI3K/AKT pathway - Linlin Zhang; Lu Chen; Dayong Tao; Fuchang Yu; Meng Qi; Shiwen Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Performance of wetland applied to ecological remediation of abandoned fish ponds: A case study in Gonghu Bay, Tai lake - Linlin Li; Jing Zhang; Shaoyong Lu; Hongbin Lu; Zhichao Du; Bin Bi; Fengmei Cao; Weijing Kong (Chemosphere, 2023)

Straw type and returning amount affects SOC fractions and Fe/Al oxides in a rice-wheat rotation system - Linlin Dong; Haihou Wang; Yuan Shen; Lingqing Wang; Haidong Zhang; Linlin Shi; Changying Lu; Mingxing Shen (Applied Soil Ecology, 2023)

Comparison of nitrogen removal performance and mechanism from low-polluted wastewater by constructed wetlands with two oxygen supply strategies: Tidal flow and intermittent aeration - Linlin Li; Jing Zhang; Qiuyue Shi; Shaoyong Lu (Chemosphere, 2023)

Crop type mapping in the central part of the North China Plain using Sentinel-2 time series and machine learning - Ke Luo; Linlin Lu; Yanhua Xie; Fang Chen; Fang Yin; Qingting Li (Computers and Electronics in Agriculture, 2023)

Convolutional neural networks (CNNs)-based multi-category damage detection and recognition of high-speed rail (HSR) reinforced concrete (RC) bridges using test images - Lingkun Chen; Wenxin Chen; Lu Wang; Chencheng Zhai; Xiaolun Hu; Linlin Sun; Yuan Tian; Xiaoming Huang; Lizhong Jiang (Engineering Structures, 2023)

Current recycling strategies and high-value utilization of waste cotton - Linlin Lu; Wei Fan; Xue Meng; Lili Xue; Shengbo Ge; Chen Wang; Shin Ying Foong; Cindy S.Y. Tan; Christian Sonne; Mortaza Aghbashlo; Meisam Tabatabaei; Su Shiung Lam (Science of The Total Environment, 2023)

Distinctive roles of land-use efficiency in sustainable development goals: An investigation of trade-offs and synergies in China - Wen Song; Shisong Cao; Mingyi Du; Linlin Lu (Journal of Cleaner Production, 2023)

Estimating small structural motions from multi-view video measurement - Enjian Cai; Yi Zhang; Xiaodong Ji; Xinzheng Lu; Linlin Xie; Yuncheng Zhuang; Taisen Zhao; Guangwei Lin (Engineering Structures, 2023)

TRIM11, a new target of p53, facilitates the migration and invasion of nasopharyngeal carcinoma cells - Ziyi Zhao; Jinkuang Deng; Ming Lu; Jun Yang; Linlin Chen; DianYuan Li; Yi Sang (Molecular Biology Reports, 2023)
Background Although tripartite motif-containing protein 11 (TRIM11) is known to be associated with a variety of cancers, its role in nasopharyngeal carcinoma (NPC) is unclear. Methods and results To investigate the role of TRIM11 in NPC, TRIM11 was stably overexpressed in 6–10B and CNE2 cells with lentiviral vectors and knocked down in S18 and 5–8F cells using the CRISPR/Cas9 system. Transwell assays and wound-healing assays revealed that TRIM11 facilitated the migration and invasion of NPC cells. Mechanistically, we found that p53 inhibits TRIM11 expression by binding to its promoter. Conclusions TRIM11 may serve as a potential diagnostic marker for NPC and has a certain therapeutic value.

Improving precipitation ensemble forecasts of typhoon heavy rainfall over East China with a modified probability-matching technique - Chun Liu; Hanqing Deng; Xuexing Qiu; Linlin Zheng; Yajun Lu; Ying Zhang (Bulletin of Atmospheric Science and Technology, 2022)

Estimating the impacts of climate change on the habitat suitability of common minke whales integrating local adaptation - Bin Sun; Linlin Zhao; Fei Shao; Zhichuang Lu; Jiashen Tian; Changdong Liu (Frontiers in Marine Science, 2022)
Climate change is exerting unprecedented effects on the habitats of marine mammals. Common minke whales ( Balaenoptera acutorostrata ) have suffered immense harm from commercial whaling, and the recovery of this species is likely threatened by climate change. To better manage and conserve this species, it is important to predict its current habitat distribution and the potential change under future climate change scenarios. Such predictions are typically generated by species distribution models (SDMs), which construct a correlation between species occurrence data and its habitat environmental variables. SDMs are commonly constructed at the species level, assuming a homogenous response of the species to climatic variables across their entire geographic range. Spatially segregated populations from the same species inhabit distinct environments and gradually adapt to the local conditions, resulting in niche differentiation among populations. Species-level SDMs that ignore the effects of local adaptation mask differences in population responses to climate change and might present an unrealistic picture of potential species distributions. Based on morphological and genetic evidence, the common minke whale was divided into three populations: the North Atlantic population (NAP), Southern Hemisphere population (SHP) and North Pacific population (NPP); these populations inhabit isolated geographic areas with distinct environmental conditions. We quantified the realized niches of these populations and found evidence of significant ecological niche differentiation. We then constructed SDMs at the species and population levels and compared the predictions from these two types of models under different climate change scenarios. Both types of models projected similar change trends in species range, with a contraction of future suitable habitats for the NAP and SHP and an expansion for the NPP. However, the magnitudes of this change differed; the population-level model projected more optimistic results for the SHP and NAP, indicating less habitat loss. This study highlighted the importance of considering local adaptation when estimating the impact of climate change on species habitat suitability. These spatiotemporal predictions provide essential knowledge for designing climate-adaptive conservation and management strategies, such as the delimitation of mobile marine protected areas (MPAs).

Construction of a mutant Bacillus subtilis strain for high purity poly-γ-glutamic acid production - Linlin He; Lu Liu; Rui Ban (Biotechnology Letters, 2022)

Statin therapy protects against abdominal aortic aneurysms by inducing the accumulation of regulatory T cells in ApoE−/− mice - Linlin Meng; Yue Lu; Xinlu Wang; Wenhai Sui; Xiao Ge; Ming Zhong; Xiao Meng; Yun Zhang (Journal of Molecular Medicine, 2022)

The involvement of oxidative stress, neuronal lesions, neurotransmission impairment, and neuroinflammation in acrylamide-induced neurotoxicity in C57/BL6 mice - Mengyao Zhao; Linlin Deng; Xiaoxuan Lu; Liqiang Fan; Yang Zhu; Liming Zhao (Environmental Science and Pollution Research, 2022)

p53 m6A modulation sensitizes hepatocellular carcinoma to apatinib through apoptosis - Weiwei Ke; Linlin Zhang; Xiangxuan Zhao; Zaiming Lu (Apoptosis, 2022)

The lag effect of 24-year tobacco consumption on lung cancer mortality in Henan Province, China, 1992 to 2016 - Linlin Li; Jie Lu; Xin Dai; Li Ma; Chongjian Wang; Liyun Feng (Environmental Science and Pollution Research, 2022)

Full-Length Transcriptome of the Whale Shark (Rhincodon typus) Facilitates the Genome Information - Fangrui Lou; Li Wang; Zhiyang Wang; Lei Wang; Linlin Zhao; Qingjie Zhou; Zhichuang Lu; Yongzheng Tang (Frontiers in Marine Science, 2022)
Rhincodon typus is a keystone and indicator species in marine ecosystems. Meanwhile, R. typus has been listed on the IUCN red list of vulnerable species. Here we used ONT platform to determine the full-length (FL) transcriptome of R. typus and obtained 14,930 FL transcripts. Among all FL transcripts, 14,915 transcripts were covered 11,892 genetic loci and 1,642 novel genetic loci were further found. Meanwhile, we identified 714 novel transcripts by compared FL transcripts with the R. typus genome. Based on FL transcripts, we also predicted the distribution patterns of ASs, LncRNAs, polyAs, CDSs and methylation sites on FL transcriptome of R. typus . Furthermore, a total of 31,021 (97.86%) CDSs can obtained annotation information. Overall, our work firstly provided the FL transcriptome and these sequences complete the annotated R. typus genome information. Furthermore, these information are a potential resource to study biological processes of R. typus .

Genetic background and cis-organization regulate ALDH7B4 gene expression in Eutrema salsugineum: a promoter analysis case study - Quancan Hou; Tianye Zhang; Wei Zhao; Linlin Wang; Lu Lu; Yuchen Qi; Dorothea Bartels (Planta, 2022)

Intensification of Downslope Nutrient Transport and Associated Biological Responses Over the Northeastern South China Sea During Wind-Driven Downwelling: A Modeling Study - Aiqin Han; Jianping Gan; Minhan Dai; Zhongming Lu; Linlin Liang; Xiaozheng Zhao (Frontiers in Marine Science, 2021)
Coastal downwelling is generally considered to have a limited biological effect compared with coastal upwelling. In this study, downslope transport of nearshore, nutrient-enriched waters during downwelling is found to induce distinct biological productivity in the water column over the northeastern South China Sea (NSCS). By conducting a process-driven study over a widened shelf with intensified downwelling in the NSCS, we investigated the biophysical processes associated with strong nutrient enrichment in the water column of downwelled waters. These processes and underlying mechanisms are largely unreported and remain unclear. Field measurements and a three-dimensional coupled physical-biological model incorporating nitrate ( N ), phytoplankton ( P ), zooplankton ( Z ), and detritus ( D ) were utilized to investigate distinct cross-shore nutrient transport over the uniquely widened NSCS shelf. We revealed that intensified downwelling circulation, dynamically induced by the widened shelf topography, enhanced chlorophyll a and biological productivity in a strip of well-mixed water over the inner shelf as well as in the downwelled water over the mid-shelf. Strong time lags and spatial differences existed among N , P , and Z because of the physical transport and the ensuing biogeochemical response. The intensified downslope transport of nutrient-rich coastal water formed distinct cross-shore wedge-shaped P , Z , and D structures, while N was rapidly consumed in the water column. This study illustrates the underlying coupled physical-biogeochemical processes associated with the observed biogeochemical response to wind-driven downwelling circulation over the variable shelf, which are commonly found in coastal oceans worldwide.

Occurrence, spatial distribution, source, and ecological risk assessment of organochlorine pesticides in Dongting Lake, China - Fengmei Cao; Zhaozhao Li; Qi He; Shaoyong Lu; Pan Qin; Linlin Li (Environmental Science and Pollution Research, 2021)

Spring phenology outweighed climate change in determining autumn phenology on the Tibetan Plateau - Jie Peng; Chaoyang Wu; Xiaoyue Wang; Linlin Lu (International Journal of Climatology, 2021)
As the third pole of the Earth, the Tibetan Plateau (TP) is highly sensitive to climate change. Phenological changes in spring (i.e., the start of the growing season, SOS) over the TP are of much debate, while our understanding on the variation of autumn phenology (i.e., the end of the growing season, EOS) is still lacking. Given the significance of tracing the latest variation of EOS induced by the ongoing global change, we used the currently longest time series (1982–2018) of the normalized difference vegetation index of the Long Term Data Record from the Advanced Very High Resolution Radiometer (AVHRR LTDR NDVI) and investigated the responses of EOS to biological and climatic factors. We found that the EOS showed an insignificantly delayed trend at an average rate of 0.14 days·decade −1 on the TP. This variation was found for all vegetation types except for alpine sparse vegetation. We further showed that spring SOS had the largest contribution to the interannual variations in EOS, where 46.5% of the vegetated areas showed significantly positive correlations between SOS and EOS ( p

Dynamic features of near-inertial oscillations in the Northwestern Pacific derived from mooring observations from 2015 to 2018 - Shijian Hu; Lingling Liu; Cong Guan; Linlin Zhang; Jianing Wang; Qingye Wang; Jie Ma; Fujun Wang; Fan Jia; Junqiao Feng; Xi Lu; Fan Wang; et al. (Journal of Oceanology and Limnology, 2020)

An Improved Coal Permeability Model with Variable Cleat Width and Klinkenberg Coefficient - Gang Wang; Zhiyong Xiao; Junhong Yu; Lu Zhang; Linlin Sun (Geotechnical and Geological Engineering, 2020)

Quality by Design–Based Assessment for Analytical Similarity of Adalimumab Biosimilar HLX03 to Humira® - Erhui Zhang; Liqi Xie; Peilan Qin; Lihong Lu; Yanpeng Xu; Wenyuan Gao; Linlin Wang; Michael Hongwei Xie; Weidong Jiang; Scott Liu (The AAPS Journal, 2020)
Quality by design (QbD) is an efficient but challenging approach for the development of biosimilar due to the complex relationship among process, quality, and efficacy. Here, the analytical similarity of adalimumab biosimilar HLX03 to Humira® was successfully established following a QbD quality study. Quality target product profile (QTPP) of HLX03 was first generated according to the public available information and initial characterization of 3 batches of Humira®. The critical quality attributes (CQAs) were then identified through risk assessment according to impact of each quality attribute on efficacy and safety. The anticipated range for each CQA was derived from similarity acceptance range and/or the corresponding regulatory guidelines. Finally, a panel of advanced and orthogonal physicochemical and functional tests and comparison of 6 batches of HLX03 and 10 batches of the reference standard demonstrated high similarity of HLX03 to Humira®, except for slightly lower percentage of high mannosylated glycans (%HM) in HLX03 which had no effect on FcγRIII binding and antibody-dependent cell-mediated cytotoxicity (ADCC) activity in human peripheral blood mononuclear cell (PBMC). All above demonstrated the feasibility and efficiency of QbD-based similarity assessment of a biosimilar monoclonal antibody (mAb).

Interaction between CA repeat microsatellites and HIF1α regulated the transcriptional activity of porcine IGF1 promoter - Hongwei Geng; Linlin Hao; Yunyun Cheng; Chunli Wang; Shan Huang; Wenzhen Wei; Rui Yang; Haoyang Li; Songcai Liu; Hao Yu; Huayi Lu (Journal of Applied Genetics, 2020)

A study of the coupled bioelectrochemical system-upflow anaerobic sludge blanket for efficient transformation of 2,4-dichloronitrobenzene - Hui Chen; Donghui Lu; Linlin Chen; Caiqin Wang; Xiangyang Xu; Liang Zhu (Environmental Science and Pollution Research, 2019)

Contribution of heterotrophic bacterioplankton to cyanobacterial bloom formation in a tributary backwater area of the Three Gorges Reservoir, China - Lunhui Lu; Linlin Xu; Jixiang Yang; Zhe Li; Jinsong Guo; Yan Xiao; Juanjuan Yao (Environmental Science and Pollution Research, 2018)

Tissue Distribution and Gender-Specific Protein Expression of Cytochrome P450 in five Mouse Genotypes with a Background of FVB - Jiamei M. Chen; Qisong S. Zhang; Xiaoyan Y. Li; Xia Gong; Yanjiao J. Ruan; Sijing J. Zeng; Linlin L. Lu; Xiaoxiao X. Qi; Ying Wang; Ming Hu; Lijun J. Zhu; Zhongqiu Q. Liu (Pharmaceutical Research, 2018)

Disposition of Flavonoids for Personal Intake - Shuqiang Liu; Haihui Zheng; Rongjin Sun; Huangyu Jiang; Jiamei Chen; Jia Yu; Qisong Zhang; Qingwei Chen; Lijun Zhu; Ming Hu; Linlin Lu; Zhongqiu Liu (Current Pharmacology Reports, 2017)

A Selenium-Enriched Ziyang Green Tea Polysaccharide Induces Bax-Dependent Mitochondrial Apoptosis and Inhibits TGF-β1-Stimulated Collagen Expression in Human Keloid Fibroblasts via NG2 Inactivation - Lele Lu; Linlin Chai; Wenping Wang; Xi Yuan; Shirong Li; Chuan Cao (Biological Trace Element Research, 2017)

Characterization of Gastric Microbiota in Twins - Quanjiang Dong; Yongning Xin; Lili Wang; Xinying Meng; Xinjuan Yu; Linlin Lu; Shiying Xuan (Current Microbiology, 2017)

In Vivo Exposure of Kaempferol Is Driven by Phase II Metabolic Enzymes and Efflux Transporters - Liang Zheng; Lijun Zhu; Min Zhao; Jian Shi; Yuhuan Li; Jia Yu; Huangyu Jiang; Jinjun Wu; Yunli Tong; Yuting Liu; Ming Hu; Linlin Lu; et al. (The AAPS Journal, 2016)

Antiviral effects of Stichopus japonicus acid mucopolysaccharide on hepatitis B virus transgenic mice - Yongning Xin; Wei Li; Linlin Lu; Li Zhou; David W. Victor; Shiying Xuan (Journal of Ocean University of China, 2016)

Distribution and linkage disequilibrium analysis of polymorphisms of GH1 gene in different populations of pigs associated with body size - YUNYUN CHENG; SONGCAI LIU; DAN SU; CHAO LU; XIN ZHANG; QINGYAN WU; SIMING LI; HAOYU FU; HAO YU; LINLIN HAO (Journal of Genetics, 2016)

Forward modeling analyses of Qilian Juniper (Sabina przewalskii) growth in response to climate factors in different regions of the Qilian Mountains, northwestern China - Junzhou Zhang; Xiaohua Gou; Yongxiang Zhang; Ming Lu; Xiangyu Xu; Fen Zhang; Wenhuo Liu; Linlin Gao (Trees, 2016)

Triple Recycling Processes Impact Systemic and Local Bioavailability of Orally Administered Flavonoids - Peimin Dai; Lijun Zhu; Feifei Luo; Linlin Lu; Qiang Li; Liping Wang; Ying Wang; Xinchun Wang; Ming Hu; Zhongqiu Liu (The AAPS Journal, 2015)

Significantly Decreased and More Variable Expression of Major CYPs and UGTs in Liver Microsomes Prepared from HBV-Positive Human Hepatocellular Carcinoma and Matched Pericarcinomatous Tissues Determined Using an Isotope Label-free UPLC-MS/MS Method - Tongmeng Yan; Song Gao; Xiaojuan Peng; Jian Shi; Cong Xie; Qiang Li; Linlin Lu; Ying Wang; Fuyuan Zhou; Zhongqiu Liu; Ming Hu (Pharmaceutical Research, 2015)

Identification of Novel MicroRNA Signatures Linked to Experimental Autoimmune Myasthenia Gravis Pathogenesis: Down-Regulated miR-145 Promotes Pathogenetic Th17 Cell Response - Jiao Wang; Shuangshuang Zheng; Ning Xin; Changxin Dou; Linlin Fu; Xiuying Zhang; Jing Chen; Yanyan Zhang; Deqin Geng; Chenghua Xiao; Guiyun Cui; Xia Shen; et al. (Journal of Neuroimmune Pharmacology, 2013)

Lanthanum chloride impairs spatial learning and memory and downregulates NF-κB signalling pathway in rats - Linlin Zheng; Jinghua Yang; Qiufang Liu; Fei Yu; Shengwen Wu; Cuihong Jin; Xiaobo Lu; Lifeng Zhang; Yanqiu Du; Qi Xi; Yuan Cai (Archives of Toxicology, 2013)

Potential short-term effects of yak and Tibetan sheep dung on greenhouse gas emissions in two alpine grassland soils under laboratory conditions - Yanjiang Cai; Xiaodan Wang; Weixin Ding; Linlin Tian; Hui Zhao; Xuyang Lu (Biology and Fertility of Soils, 2013)

Assessment of the SeaWinds scatterometer for vegetation phenology monitoring across China - Linlin Lu; Huadong Guo; Cuizhen Wang; Qingting Li (International Journal of Remote Sensing, 2013)

PEGylated Multi-Walled Carbon Nanotubes for Encapsulation and Sustained Release of Oxaliplatin - Linlin Wu; Changjun Man; Hong Wang; Xiaohe Lu; Qinghai Ma; Yu Cai; Wanshan Ma (Pharmaceutical Research, 2013)

Overexpression of GbWRKY1 positively regulates the Pi starvation response by alteration of auxin sensitivity in Arabidopsis - Li Xu; Li Jin; Lu Long; Linlin Liu; Xin He; Wei Gao; Longfu Zhu; Xianlong Zhang (Plant Cell Reports, 2012)